Characterization of the cholangiocarcinoma drug pemigatinib against FGFR gatekeeper mutants - Qianmeng Lin; Xiaojuan Chen; Lingzhi Qu; Ming Guo; Hudie Wei; Shuyan Dai; Longying Jiang; Yongheng Chen (Communications Chemistry, 2022)
Pemigatinib is an FDA-approved drug for the treatment of cholangiocarcinoma, but while it is known to target fibroblast growth factor receptors, its mechanism of action is still not fully understood. Here, biochemical and structural analyses reveal that pemigatinib is a potent and selective FGFR1–3 inhibitor, and has excellent potency against the Val-to-Ile gatekeeper mutation.